The Relationship between Health Literacy and Healthy Food Consumption Behaviors for Obesity Prevention among Female High School Students in Thung Song District, Nakhon Si Thammarat Province - Thongkrachang, Kanyamani; Pengpid, Supa; Jayasvasti Chantarasongsuk, Isareethika (Disease Control Journal, 2025)
Health literacy in selecting healthy foods is a critical factor in preventing obesity among adolescent girls, aligning with the Ministry of Public Health’s strategic plan to promote adolescent health. This cross-sectional survey aimed to assess the level of health literacy and its association with healthy food selection behaviors for obesity prevention among female high school students in Thung Song District, Nakhon Si Thammarat Province. A total of 350 students participated in this survey, and data were collected using a structured questionnaire with item-content validity indices ranging from 0.66 to 1.00 and Cronbach’s alpha coefficients of 0.88 and 0.79. Data were analyzed using descriptive statistics and inferential statistics, including Spearman’s rank correlation coefficient. The overall health literacy level was found to be adequate (mean=84.75±10.33). When examined by component, access to health information and services for obesity prevention (mean=25.90±3.81), communication for enhancing obesity prevention skills (mean=19.37±2.86), media and information literacy (mean=14.81±2.97), management of personal health conditions (mean=11.05±2.40), and health knowledge and understanding (mean=3.14±0.85) were all at an adequate level. However, decision-making for proper obesity prevention behaviors was insufficient (mean=10.47±2.24). In addition, access to health information and services was positively associated with healthy food selection behaviors (r=0.17, p=0.00). Although most students exhibited adequate health literacy, decision-making skills remained insufficient. Therefore, promoting and developing analytical and decision-making skills through practical activities and appropriate media is recommended to enable students to translate knowledge into correct and sustainable obesity-prevention practices.